PENGARUH KONSELING ISLAM DALAM MENINGKATKAN KESADARAN SHOLAT BERJAMAAH SISWA - Widia Wati; Silvianetri Silvianetri (IAIN Batusangkar, 2018)
The fundamental religious problems experienced by students today are the low awareness of prayers in congregation. One technique that can be used to increase awareness is to do the prayers in congregation through Islamic counseling. To reveal this in this study using the experimental method, specifically one group pretest-posttes. The research sample consisted of 25 students from SMAN 1 Pasaman. The instrument used was the student prayer awareness scale and data analysis using the t-test. The results revealed that: (1) there was an increase in students' awareness of prayers in congregation after being given a classical format Islamic counseling treatment with an average pretest of 46.04 points, which was in the low category, and posttest 58.76 points, in the high category, and a difference of 12.72 points , (2) there is the influence of Islamic counseling on increasing awareness of student prayer in congregation. Based on the results of this study it is recommended for counselors in schools to be able to apply Islamic counseling as a treatment for increasing student prayer awareness.